Revealing Household Economic Welfare and Resilience - Suwena, Kadek Rai; Heryanda, Komang Krisna; Irwansyah, M. Rudi (Jurnal Ekonomi Kuantitatif Terapan; 2023: Vol. 16, No. 2, Agustus 2023 (pp.187-360)DO - 10.24843/JEKT.2023.v16.i02.p09, 2023)
Prosperity provides opportunities for households to achieve economic resilience. Economic resilience is a condition and ability to recover and rise from problems in economic aspects. The welfare condition of women in freelance daily labor households in Tiyingtali Village has not been able to reflect the economic resilience of households. This research reveals the motivation and role of women in Tiyingtali Village who work as casual daily laborers in the household to achieve prosperity and economic resilience. By using a qualitative approach, these two problems become a complex thing to discuss. Through qualitative analysis with stages: 1) data collection; 2) Data reduction; 3) Presentation of data; 4) Conclusion drawing/Verification, the welfare and economic resilience problems of women's freelance daily laborer households can be explained. To ensure the validity of the research data obtained, triangulation of sources is then carried out. Research findings show that "Gunakaya" (fighting spirit to have wealth alone or with husband) is a motivation. This motivation leads to the condition of a prosperous family. Not having savings for supplies, makes for a lack of household economic resilience. The inability of freelance daily working women to set aside their income makes it an obstacle to realizing household economic resilience. Efforts to fulfill the household economy of husband and wife must help each other to create economic resilience.